The Significance of the Shopee Member Hierarchy in Social Reality and the Consumerist Lifestyle of Society - Riska Alya Ramadhana (Universitas Sebelas Maret (UNS), 2026)
The digital economic transformation has shifted consumer behavior from merely fulfilling needs to a space for interpreting symbols of social status. This phenomenon is evident in Shopee’s membership tiers (Silver, Gold, and Platinum), which reproduce social stratification through symbols of a digital caste system. Surakarta, as a city of education and diverse economy, serves as a meeting point for various social backgrounds, offering insights into consumption patterns stemming from the broader diversity of digital consumer behavior. Therefore, this study aims to critically analyze the representation of social stratification in the digital realm through Shopee Member features using Stuart Hall’s theory of representation and Jean Baudrillard’s theory of hyperreality. This study employs a qualitative descriptive research method with a case study approach. Data collection techniques include in-depth interviews, digital observation, literature review, and documentation. Informant selection uses a purposive sampling technique. To ensure data validity, this study employed source triangulation, while data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that the Shopee Member features successfully reproduce a new social hierarchy that blurs the boundaries between real needs and illusory images. At the Silver level, user identity is still grounded in rational utility. Meanwhile, the Gold category begins to reveal the ambiguity of a transitional class, where status is gradually attained through consumption activities. At the pinnacle, the Platinum category reflects a hyperreality in which the digital image and privileges associated with the badge are perceived as more real than their actual utility.